Exosomes from tendon stem cells promote injury tendon healing through balancing synthesis and degradation of the tendon extracellular matrix. Issue 8 (31st May 2019) - Wang, Yunjiao; He, Gang; Guo, Yupeng; Tang, Hong; Shi, Youxing; Bian, Xuting; Zhu, Min; Kang, Xia; Zhou, Mei; Lyu, Jingtong; Yang, Mingyu; Mu, Miduo; et al.
Abstract: Tendon injuries are common musculoskeletal system disorders in clinical, but the regeneration ability of tendon is limited. Tendon stem cells (TSCs) have shown promising effect on tissue engineering and been used for the treatment of tendon injury. Exosomes that serve as genetic information carriers have been implicated in many diseases and physiological processes, but effect of exosomes from TSCs on tendon injury repair is unclear. The aim of this study is to make clear that the effect of exosomes from TSCs on tendon injury healing. Exosomes were harvested from conditioned culture media of TSCs by a sequential centrifugation process. Rat Achilles tendon tendinopathy model was established by collagenase‐I injection. This was followed by intra‐Achilles‐tendon injection with TSCs or exosomes. Tendon healing and matrix degradation were evaluated by histology analysis and biomechanical test at the post‐injury 5 weeks. In vitro, TSCs treated with interleukin 1 beta were added by conditioned medium including exosomes or not, or by exosomes or not. Tendon matrix related markers and tenogenesis related markers were measured by immunostaining and western blot. We found that TSCs injection and exosomes injection significantly decreased matrix metalloproteinases (MMP)‐3 expression, increased expression of tissue inhibitor of metalloproteinase‐3 (TIMP‐3) and Col‐1a1, and increased biomechanical properties of the ultimate stress and maximum loading. In vitro, conditioned medium with exosomes and exosomes also significantly decreased MMP‐3, and increased expression of tenomodulin, Col‐1a1 and TIMP‐3. Exosomes from TSCs could be an ideal therapeutic strategy in tendon injury healing for its balancing tendon extracellular matrix and promoting the tenogenesis of TSCs.